Fostering Community Resilience through Social Capital - Ilham Nur Hanifan Maulana; Tasya Fiane Wardah (University of Merdeka Malang, 2023)
An experienced and resilient community has become a much-studied discourse after COVID-19. Strengthening the ability to self-organize post-crisis events encountered difficulties around changing local risk perspectives. In addition, they are increasing the capacity of individuals as a whole to form the expected community resilience. This study explains the importance of leveraging social capital to increase community capacity, affecting the ability to survive future crises. This study used a literature review to explore prior conceptions and conclusions about fostering community resilience and essential agreement of social capital. In this research, we seek a contribution through the following arguments a) Community resilience is the outcome of reciprocity social relationships; b) Social capital is an endeavor to cultivate relationships that encourage shared-value advantages between community members; c) Intellectual capital is the valuable sources in representing action-based of knowledge. The result shows it is necessary to build community resilience through a robust social approach, maintaining and reconstructing social capital to present community advantage and shared-value embedded in each community member.